Sulfate Resistance in Cements Bearing Bottom Ash from Biomass-Fired Electric Power Plants - José M. Medina; María Isabel Sánchez de Rojas; Isabel F. Sáez del Bosque; Moisés Frías; César Medina (Applied Sciences, 2020)
To address some of the gaps in the present understanding of the behavior of new supplementary cementitious materials such as bottom ash (BA) from biomass-fired electric power plants in cement manufacture, this study explored the effect of this promising material on the sulfate resistance of the end product. Cement paste prepared with 10% or 20% (previously characterized for mineralogy and chemical composition) BA was Köch–Steinegger tested for sulfate resistance. The hydration products, in turn, were analyzed before and after soaking the reference and experimental cements in sodium sulfate to determine whether the use of the addition hastened microstructural, mineralogical, or morphological decay in the material. The 56 days findings showed that the presence of BA raised binder resistance to sulfate attack. Köch–Steinegger corrosion indices of 1.29 and 1.27 for blended cements OPC + 10 BA and OPC + 20 BA, respectively, were higher than the 1.26 recorded for ordinary Portland cement (OPC). In addition, weight gain was 20.5% and volume expansion was 28.5% lower in the new materials compared to OPC. The products resulting from the external sulfate-cement interaction, gypsum and ettringite, were deposited primarily in the pores present in the pastes. The conclusion drawn is that binders bearing 10% or 20% BA are, a priori, apt for use in the design and construction of cement-based elements exposed to sulfate-laden environments.